2023
DOI: 10.3390/biology12081091
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Understanding of Microglia and Border-Associated Macrophages

Abstract: The central nervous system (CNS) plays a crucial role in regulating bodily functions by sensing and integrating environmental cues and maintaining proper physiological conditions. Recent research has revealed that CNS functions are closely coordinated with the immune system. As even minor disturbances of the immune system in the CNS can lead to various dysfunctions, diseases, or even death, it is highly specialized and segregated from that in peripheral regions. Microglia in the parenchyma and macrophages at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…Staining in the skeletal muscle was associated with small cells on the surface of muscle fibers, consistent with muscle resident macrophages known to express high levels of CD163 and originate from both embryonic yolk sac and liver, as well as postnatally from blood monocytes ( Wang et al, 2020 ). In the brain, positive staining for CD163 was largely restricted to the pia mater, which is known to contain border associated macrophages ( Taketomi and Tsuruta, 2023 ). The apparent lack of staining in the neural parenchyma is consistent with prior observations which show an absence of macrophages in the cerebrum and cerebellum during late gestation ( Matsumoto and Ikuta, 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…Staining in the skeletal muscle was associated with small cells on the surface of muscle fibers, consistent with muscle resident macrophages known to express high levels of CD163 and originate from both embryonic yolk sac and liver, as well as postnatally from blood monocytes ( Wang et al, 2020 ). In the brain, positive staining for CD163 was largely restricted to the pia mater, which is known to contain border associated macrophages ( Taketomi and Tsuruta, 2023 ). The apparent lack of staining in the neural parenchyma is consistent with prior observations which show an absence of macrophages in the cerebrum and cerebellum during late gestation ( Matsumoto and Ikuta, 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, adult microglia have branched projections and cell bodies, but they enter an activated state and change morphology in response to stimuli, aging, or progressive CNS pathology. Recent studies have reported heterogeneous populations of microglia in the brain across organisms of different lifespans, sexes, and species [42,43]. Transcriptome analysis showed that microglia in female mice show an advancing aging process in each stage, while microglia in male mice switch abruptly to an aging phenotype at 12 months.…”
Section: Microglial Senescencementioning
confidence: 99%